Environmental Impact Analysis of Methane Gas from Landfill using LCA in Klotok landfill, Kediri, East Java - Restu Hikmah Ayu Murti; Muhammad Abdus Salam Jawwad; Syadzadhiya Qothrunada Zakiyayasin Nisa; Rizka Novembrianto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The effective management of municipal solid waste is a persistent challenge within emerging nations. The observed phenomenon can be attributed to a multitude of reasons, encompassing swift economic growth, urban population development, garbage output, the substantial costs associated with waste treatment, and the design and functionality of containment systems. Methane, being the second most significant greenhouse gas following carbon dioxide, is prominently emitted into the environment by municipal solid waste dumps. This study use the IPCC model to assess the methane emissions generated by landfills. Additionally, Simapro 9.5 software is utilised in conjunction with the ReCiPe 2016 Midpoint approach to evaluate the corresponding environmental consequences. The Klotok landfill was found to generate the maximum quantity of methane, specifically 3.518 Mg CO2 eq, as determined by the composition analysis of paper waste. Additionally, the largest environmental impact was observed in the category of human toxicity carcinogenicity, as indicated by the life cycle assessment (LCA) analysis with a value of 3733.057.